Alternative mechanisms of miR-34a regulation in cancer - Slabáková, Eva; Culig, Zoran; Remšík, Ján; Souček, Karel (Cell death & disease, 2017)
MicroRNA miR-34a is recognized as a master regulator of tumor suppression. The strategy of miR-34a replacement has been investigated in clinical trials as the first attempt of miRNA application in cancer treatment. However, emerging outcomes promote the re-evaluation of existing knowledge and urge the need for better understanding the complex biological role of miR-34a. The targets of miR-34a encompass numerous regulators of cancer cell proliferation, survival and resistance to therapy. MiR-34a expression is transcriptionally controlled by p53, a crucial tumor suppressor pathway, often disrupted in cancer. Moreover, miR-34a abundance is fine-tuned by context-dependent feedback loops. The function and effects of exogenously delivered or re-expressed miR-34a on the background of defective p53 therefore remain prominent issues in miR-34a based therapy. In this work, we review p53-independent mechanisms regulating the expression of miR-34a. Aside from molecules directly interacting with MIR34A promoter, processes affecting epigenetic regulation and miRNA maturation are discussed. Multiple mechanisms operate in the context of cancer-associated phenomena, such as aberrant oncogene signaling, EMT or inflammation. Since p53-dependent tumor-suppressive mechanisms are disturbed in a substantial proportion of malignancies, we summarize the effects of miR-34a modulation in cell and animal models in the clinically relevant context of disrupted or insufficient p53 function.
Keywords: regulace genové exprese u nádorů; Animals; Tumor Suppressor Protein p53; tumor supresorové geny; Epithelial-Mesenchymal Transition; Neoplasms; Gene Expression Regulation, Neoplastic; nádory; lidé; epigeneze genetická; mikro RNA; nádorový supresorový protein p53; MicroRNAs; epitelo-mezenchymální tranzice; promotorové oblasti (genetika); zvířata; Promoter Regions, Genetic; Epigenesis, Genetic; Genes, Tumor Suppressor; Humans